DESAIN DAN PEMBUATAN HAND LOADER OUTPUT DENGAN MENGGUNAKAN SOFTWARE SOLIDWORKS - Yueprayuga, Abie; Puspawan, Angky; Nuramal, Agus; Hadi Susanto, Tri Nugroho (Rekayasa Mekanika: Jurnal Ilmiah Teknik Mesin, 2025)
The design of this output hand loader aims to be a place to receive samples that have passed testing in order to improve ergonomics during the irradiation sampling process by utilizing existing materials (acrylic). The hand loader output testing method is by calculating the travel time for empty capsules and capsules containing five variations of samples when sent from the pneumatic lab to the AAN lab, and followed by testing the functional integrity of the capsules when transferred. The results show that the travel time required for the capsule to reach the hand loader is 2 seconds and the capsule is not damaged, broken or other defects. The conclusions obtained from the design of the output hand loader were the design and use of acrylic material that did not damage the capsules during testing and improved ergonomics during the sampling process compared to the previous sampling site. Apart from that, the problem when making an output hand loader lies in making bolt holes that are not parallel to other parts, which requires making new holes.